American Complete Streets and Australian SmartRoads: What Can We Learn from Each Other?. Issue 39 (December 2018) - Delbosc, Alexa; Reynolds, James; Marshall, Wesley; Wall, Andrew
Road management in both Australasia and America has historically focused on facilitating vehicle movement and reducing congestion. More recently, however, there has been a shift to acknowledge the wider role that roads play in society. Road safety, equity impacts, considerations of "place" and the needs of different road users (including transit, pedestrians, and cyclists) are all gaining prominence. Two relatively new approaches to road design and management—Complete Streets in the United States and SmartRoads network operations planning in Australia—embody the spirit of this change. This paper summarizes the development of the Complete Streets movement in America and introduces the SmartRoads management framework, which was developed in the state of Victoria, Australia. In the SmartRoads process, roads within a network are classified in a multimodal Road User Hierarchy, network issues are identified using multimodal level of service measures, and possible operational or design solutions are compared using decision-making Network Fit Assessment software. We compare the scope, emphasis, and approach of the two frameworks; although they were developed at around the same time, the two approaches differ in significant ways. Yet the two approaches can learn from each other in order to significantly improve the management and design of roads in both Australia and the United States.